2013
DOI: 10.1097/ccm.0b013e3182742d45
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrushing for Critically Ill Mechanically Ventilated Patients

Abstract: In intubated, mechanically ventilated critically ill patients, toothbrushing did not significantly reduce the risk of ventilator-associated pneumonia overall. Toothbrushing has no effect on mortality or length of stay. Electric and manual toothbrushing seem to have similar effects. More research is needed on this aspect of oral care to evaluate its potential to decrease ventilator-associated pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 57 publications
2
40
0
3
Order By: Relevance
“…A study from Japan found a positive correlation between high salivary bacterial counts in nursing home residents and the incidence of pneumonia [7*], suggesting that intensive oral care regimens to reduce oral bacterial burden may help to prevent the onset of respiratory disease. Despite these promising results, meta-analyses have not shown significant overall benefit of enhanced oral care for the prevention of pneumonia in ventilated patients [19,20*]. A recent pilot study instituting twice daily chlorhexidine rinses and upright positioning during feeding for nursing home residents was terminated for futility when the intervention showed no significant reduction in the incidence of pneumonia [21**].…”
Section: Preventing Infectionmentioning
confidence: 99%
“…A study from Japan found a positive correlation between high salivary bacterial counts in nursing home residents and the incidence of pneumonia [7*], suggesting that intensive oral care regimens to reduce oral bacterial burden may help to prevent the onset of respiratory disease. Despite these promising results, meta-analyses have not shown significant overall benefit of enhanced oral care for the prevention of pneumonia in ventilated patients [19,20*]. A recent pilot study instituting twice daily chlorhexidine rinses and upright positioning during feeding for nursing home residents was terminated for futility when the intervention showed no significant reduction in the incidence of pneumonia [21**].…”
Section: Preventing Infectionmentioning
confidence: 99%
“…A previous study showed that oral care with chlorhexidine and dental brushing alone was not superior to oral care with chlorhexidine alone for preventing postoperative pneumonia and VAP. 28 This might indicate that chlorhexidine prevents postoperative pneumonia and VAP, and that a good level of oral health is more important than an improvement in oral hygiene. Other previous studies showed that oral care with chlorhexidine along with professional oral care was superior to oral care with chlorhexidine alone.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a marker of host immune activity in response to the elevated plaque levels and can highlight the importance of plaque scoring in critical care medicine (Wise & Williams, 2013). Oral hygiene, predominantly tooth brushing, can be effective in disrupting the plaque biofilm; however, small amounts of potentially pathogenic biomass firmly attached to the enamel surface are likely to remain (Alhazzani et al , 2013). …”
Section: Discussionmentioning
confidence: 99%